Workplace relocation and its association with car availability and commuting mode choice. (January 2022) - Pfertner, Maximilian; Büttner, Benjamin; Duran-Rodas, David; Wulfhorst, Gebhard
Abstract: The workplace location impacts both daily mobility behavior and long-term mobility decisions. Many case studies have observed significant effects of workplace relocation on car availability and mode choice to work, but there is a lack of studies that go beyond a single-company relocation to explore the association between workplace relocation and a subsequent change in car availability and car commuting, with a focus on the importance of the workplace location as an explanatory variable for these changes. In this study, we examine the associations of workplace relocation with the increase in car availability and switch to car commuting in 6404 surveyed workers in the Metropolitan Region of Munich. A subset of the data with workers who have changed their workplace location while maintaining the same residential location ( n = 787) is used to visualize the effect of the workplace relocation. By using "flow-diagrams" for a descriptive analysis of the data, a logistic regression on the increase in car availability as well as a Heckman Selection Model on the modal switch to driving, we find statistically significant associations of the workplace relocation with the increase in car availability and the change to driving. Workplace relocations to less centralized areas are associated with an increase in car availability and a change to driving. Vice versa, a relocation to a more centralized areas is negatively associated. Our results emphasize the importance of workplace locations and especially re-locations as triggers for changes in car availability and mode choice. We advocate for wisely designed planning processes and decision-making tools for analyzing and planning workplace locations, in order to make use of the window of opportunity for behavior change towards sustainable commuting and to foster well-working regional systems for living, working, and everything in between.